FIRST FIND OF OBRUCHEVELLA IN THE VENDIAN DEPOSITS OF THE MIDDLE URALS - Goloveenkok V.K.; Belova M.Yu.; Kurbatskaya F.A. (My University, 1989)
Obruchevella, because of its characteristic structure (tubules coiled into a regular cylindrical spiral), is an extremely distinctive component of many Precambrian microfossil associations. It is widespread geographically, but have nowhere been found in deposits older than Upper Riphean, in which they are represented by very small forms. In younger deposits they are considerably larger. All this enables Obruchevella to be used for biostratigraphic purposes, therefore the first find of Obruchevella in the Vendian deposits of the Middle Urals, which is also the first in the Urals as a whole, is extremely important.
Keywords: Vendian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский